(3GdHhQUI hGdHfhc GdJLGQjIs - (3eMeO UGdM(B, (3GdMfGhjs ((3GdGScfOQjg(B:s (3GdOGQ GdLGeYjg(B,s, 2000)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B:(3CShGb GdeGd h GdChQGb GdeGdjIaj GdOhd GdeJbOeI,JMOjO CSYGQ GdChQGb GdeGdjIaj GdHhQUI,Shb GdChQGb GdeGdjI aj eUQ CShGb GdGUOGQ hGdJOGhd ,GdTQcGJ GdYGedI aj eLGd GdChQGb GdeGdjI aj eUQ, bVGjG eYGUQI aj GdHhQUI GdeUQjI , GdeDSSGJ GdeGdjI , GdHfhc GdJLGQjI , GOGQI GdGUhd aj GdHfhc GdJLGQjI GOGQI fbOjI , GOGQI GdGSJKeGQGJ aj GdGhQGb GdeGdjI , GOQI GdGSJKeGQGJ aj GdbQhV , GOQGI GdNUhe aj GdHfhc GdJLGQjI , GOGQI QCS GdeGd , Jbjje GOGA GdHfhc GdJLGQjI , GdHfhc GdGSdGejI , GOdGQI GdNUhe aj GdHfhc GdGSdGejI (B.s
(3HjHdjhZQGajG U(B.419s
Keywords: (3GdGShGb GdeGdjgs; (3GdGhQGb GdeGdjgs; (3GdHhQUGJs